Analysis of Breakdown Voltage Test on Transformer Oil based on Dissolved Gas Analysis Test Result - I Made Yulistya Negara; Dimas Anton Asfani; Daniar Fahmi; Roikhana Farista Dewira; Mochammad Wahyudi; Made Yudha Pranadiksa Giri (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Transformer which has full-load and used continuously will create heat on the core, so that oil insulation is required. The impact of gases in oil insulation to breakdown voltage has been not investigated yet. This research implied an information about the impact of gases in insulation oil to breakdown voltage. Multiple linear regression with 300 data was the method used in this research. Analysis had been conducted on each gas, all gases, three combinations of gasses, four combination gases without acetylene, and three combination gases without acetylene. The target of this research was to know the impact of gases in oil transformer to the value of breakdown voltage. The results showed that the gasses had impact of 0.325 on breakdown voltage classified as a slight impact for breakdown voltage. Keywords: DGA, BDV, Transformer Oil, Double Linear Regression